Bimetallic quantum dots (Cu-Pd, Ni-Pd) catalyzed reaction of bromo arenes with alkenes and aryl boronic acids - Raut, Pallavi K.; Meroliya, Heena K.; Dumbre, Swapnil R.; Patil, Vaishali N.; Solanki, Bhanupratap S.; Waghmode, Shobha A.; Iyer, Suresh (Indian Journal of Chemistry, 2023)
Bimetallic quantum dots (Cu-Pd and Ni-Pd) are active ligand-free catalysts for the alkenylation and arylation of aryl bromides. The catalysts are easy to synthesize by benign green protocols and characterized by various techniques. The bimetallic QD catalysts synthesized thus are superior to Pd(OAc)2 or other Pd NP catalysis of alkenylation reactions of aryl bromides with similar E-selectivity. The reaction of aryl bromide with aryl boronic acid is facile with high yields.
Keywords: Aryl bromides; Bimetallic QDs catalysis; Cu-Pd; Mizoroki-Heck; Ni-Pd; Suzuki coupling